Preparation, characterisation, antioxidant and antiglycation activities of the novel polysaccharides from the pileus of Dictyophora rubrovolvata. (24th November 2016) - Sun, Liping; Bao, Changjun; Chang, Weidan; Zhuang, Yongliang
Summary: The polysaccharides from the pileus of Dictyophora rubrovolvata (DPP) were extracted by ultrasonic‐assisted extraction (UAE) and the operating parameters were optimised by orthogonal experiment. The polysaccharides were separated and purified by DEAE‐52 and Sephadex G‐100 column chromatography to obtain two fractions of DPP‐1s and DPP‐2s. The average of molecular weights, monosaccharide compositions, antioxidant and antiglycation activities of DPP‐1s and DPP‐2s were investigated. The results showed DPP‐1s and DPP‐2s had high inhibitory effects on oxidation and glycation, and DPP‐2s showed stronger bioactivity than DPP‐1s, which might be due to their differences in the molecular weight and uronic acid content. Furthermore, the UV and FTIR spectra were used to evaluate the characterisations of DPP‐2s, which demonstrated that DPP‐2s had no protein and nuclear acid with the pyranose ring structure. This study indicated that DPP‐2s could be used as a source of natural antioxidant and antiglycation components. Abstract : DPP‐2s showed high inhibitory effects on the formation of AGE with low molecular weight. DPP‐2s exhibited the pyranose ring structure without protein and nuclear acid.